Still just a geek : an annotated memoir - Wheaton, Wil (William Morrow, an imprint of HarperCollins Publishers, 2022)
The celebrated actor, personality, and all-around nerd revisits his 2004 collection of insightful and humorous blog posts, presents additional later writings, and offers all new material in which he opens up about his life, from his abusive childhood to finding his true purpose.